MnFe2O4-NH2-HKUST-1, MOF magnetic composite, as a novel sorbent for efficient dye removal: fabrication, characterization and isotherm studies - Masoumeh Mohammadnejad; Sedigheh Alizadeh (Scientific Reports, 2024)
Abstract Dye in industrial wastewater is one of the most serious environmental concerns due to its potentially harmful effects on human health. Many industrial dyes are carcinogenic, toxic and teratogenic. Removal and recovery of hazardous dyes from the effluents requires efficient adsorbents. In this study, magnetic adsorbent MnFe2O4-NH2-HKUST-1 was synthesized to remove methylene blue and crystal violet dyes from aqueous solutions. The synthesized adsorbent was characterized using FTIR, XRD, BET, VSM, SEM, TGA and Zeta potential techniques. The effect of different parameters such as pH, contact time, and adsorbent dosage on the removal of dyes was investigated. The dye adsorption process was investigated by UV–Vis spectrophotometry. The maximum adsorbent capacity was obtained as 149.25 mg/g for methylene blue and 135.13 mg/g for crystal violet. The adsorption equilibrium isotherm and kinetic models were plotted and results showed that the adsorption process for both dyes is a collection of physical and chemical adsorption based on langmuir and freundlich isotherm models, and follows the pseudo-second-order adsorption kinetics. This study shows that magnetic adsorbent MnFe2O4-NH2-HKUST-1 has a good potential for removal of methylene blue and crystal violet dyes from water in a short time (5 min) and it is easily separated from the solution by a magnetic field due to its magnetic property.